2017
DOI: 10.1074/jbc.m117.784280
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of induced pluripotent stem cells from type 1 diabetic patients enhances differentiation into functional pancreatic β cells

Abstract: Type 1 diabetes (T1D) can be managed by transplanting either the whole pancreas or isolated pancreatic islets. However, cadaveric pancreas is scarcely available for clinical use, limiting this approach. As such, there is a great need to identify alternative sources of clinically usable pancreatic tissues. Here, we used induced pluripotent stem (iPS) cells derived from patients with T1D to generate glucose-responsive, insulin-producing cells (IPCs) via 3D culture. Initially, T1D iPS cells were resistant to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
(108 reference statements)
0
33
0
Order By: Relevance
“…Human iPSC from patients with rare forms of diabetes-related metabolic disorders have similarly shown significant functional endothelial impairment 58 . Transient chemical demethylation of T1D-hiPSC was sufficient to restore differentiation in resistant cell lines and achieve functional differentiation into insulin-producing cells 18 . Naïve reversion of conventional DhiPSC may potentiate an epigenetic remodeling of reprogrammed diabetic fibroblasts that avoids differentiation into dysfunctional ECs with diabetic epigenetic memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human iPSC from patients with rare forms of diabetes-related metabolic disorders have similarly shown significant functional endothelial impairment 58 . Transient chemical demethylation of T1D-hiPSC was sufficient to restore differentiation in resistant cell lines and achieve functional differentiation into insulin-producing cells 18 . Naïve reversion of conventional DhiPSC may potentiate an epigenetic remodeling of reprogrammed diabetic fibroblasts that avoids differentiation into dysfunctional ECs with diabetic epigenetic memory.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional hiPSC adopt a spectrum of mEpiSC-like pluripotent states with highly variable lineage-primed gene expressions and post-implantation primed epiblast epigenetic marks that result in inconsistent or diminished interline differentiation potencies 12,13 . Moreover, epigenetic aberrations in diseased states such as diabetes further inhibit efficient donor cell reprogramming to functional pluripotent states [14][15][16][17][18] .…”
mentioning
confidence: 99%
“…Human iPSC from patients with rare forms of diabetes-related metabolic disorders have similarly shown significant functional endothelial impairment58 . Transient chemical demethylation of T1D-hiPSC was sufficient to restore differentiation in resistant cell lines and achieve functional differentiation into insulinproducing cells18 .In summary, these studies have demonstrated that highly functional N-VP cells can be generated independent of genetic background or diseased origin from a diseased N-hPSC.Naïve reversion of conventional DhiPSC may potentiate an epigenetic remodeling of reprogrammed diabetic fibroblasts that avoided differentiation into dysregulated in dysfunctional ECs with 'diabetic epigenetic memory'. Similarly, tankyrase inhibitor-regulated N-DhiPSC are expected to improve the poor and variable DhiPSC differentiation generation of other affected tissues in diabetes 64 including pancreatic, renal, hematopoietic, retinal, and cardiac lineages.…”
mentioning
confidence: 83%
“…Direct differentiation of iPSCs into insulin producing cells was conducted by treatment of cultured cells with WNT3A, Activin A for DE formation, and subsequent treatment with FGF10, cyclopamine and retinoic acid for formation of gut tube endoderm and pancreatic progenitors. The endocrine cells were able to respond on glucose stimulation after further differentiation by secreting C-pep- Human skin cells Integrating retroviral reprogramming Generation of insulin-producing islet-like clusters; secretion of C-peptide upon glucose stimulation [25] Adult T1D skin fibroblasts Integrating retroviral reprogramming Differentiation of patient-derived iPSCs into insulin producing cells in vitro [27] Normal mouse skin fibroblasts Integrating retroviral reprogramming Differentiation of T1D -iPSCs patients into insulin secreting β-cells; respond to glucose stimulation under physiological or pathological conditions [26] Adult T1D skin fibroblasts Integration-free transfection of synthetic mRNAs T1D-iPSCs showed upregulations of pancreas-specific microRNAs [63] Human foreskin fibroblast Polycistronic lentiviral vector Differentiation of iPSCs into β-cells promoted by over-expression of miR-375 without growth factors; iPSC-derived β-cells secreted insulin in glucose-dependent manner [33] Adult skin fibroblasts NA Growth factor-free generation of iPSC-derived islet-like cell clusters via transfection of hsa-miR-186 and hsa-miR-375 [32] Diabetes skin fibroblasts Non-integrating Sendai viral vectors Differentiation of T1D -iPSCs patients into β-cells; response to antidiabetic drugs [62] iPSC lines (253G1, 454E2, and RIKEN-2A) obtained from RIKEN cell bank -Generation of uniform population of iPSC-derived pancreatic endocrine cells via 3D approach cultured on agarose microwell plates [34] CD34 + cord blood cells EBNA-based episomal system Efficient generation of iPSC-derived pancreatic islet cells cultured on a closed channel-based culture system [35] T1D somatic cells NA Generation of high number of iPSC-derived glucose-sensitive and insulin producing cells via highly efficient 3D protocol based on demethylation strategy [36] Diabetes fibroblasts lentiviral inducible transduction system Efficient differentiation of iPSCs into glucose-responsive insulin producing cells; presence of mature endocrine secretory granules [31] tide. Jeon et al [28] generated iPSCs both from NOD mouse embryonic fibroblasts and NOD mouse pancreas-derived epithelial cells and developed a method for stepwise differentiation of NOD-iPSCs into functional pancreatic β-cells.…”
Section: Differentiation Of Escs/ Ipscs Into Pancreatic β-Cellsmentioning
confidence: 99%